Implementasi Metode Bermain Peran Dalam Menanamkan Kepercayaan Diri Anak Usia Dini di Taman Kanak-kanak, Kemala Bhayangkari 26 Kota Bengkulu - Rahma Putri, Lailatul (AT-TUFULA: Islamic Education Early Chilldhood, 2025)
This study aims to determine the implementation of the role-playing method in instilling self-confidence in early childhood has a very important role in the child's life in the future. The role-playing method in instilling children's self-confidence is an effective learning for children because with the role-playing method children can imagine, explore, create something, get new experiences, children become happy, children become optimistic, and also be tolerant. In this study the author used a descriptive qualitative research method obtained from the field. Data collection techniques are through observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. This study was conducted in classes B1, B2, and B3 at Kemala Bhayangkari Kindergarten 26 Bengkulu City with a total of 43 students.